Moldova Trade Study : Note 1. Analysis of Trade Competitiveness - World Bank (World Bank, Washington, DC, 2016)
As a small economy, Moldova’s growth and development prospects are closely related to its performance in international and regional markets. In this report the authors have looked at the export performance and competitiveness of the Moldovan economy. This report provides an overview of Moldova’s trade competitiveness. Its objectives are twofold: (i) to present a comprehensive analysis of Moldova’s recent trade performance and (ii) to identify policy measures and interventions that can enhance the competitiveness of Moldova’s export firms and the value added of their exports. The report is divided into two main parts. Part one contains an exports outcome analysis. It assesses export performance along four dimensions that contribute to form a comprehensive picture of the sustainable competitiveness of the export sector, including (i) the level, growth, and market share performance of existing exports (the “intensive margin”); (ii) diversification of products and markets (the “extensive margin”); (iii) the quality and sophistication of exports (the “quality” margin); and (iv) the survival of export flows (the “sustainability margin”). Part two investigates constraints on Moldova’s competitiveness, focusing specifically on a series of supply-side factors, such as the role of backbone and input services and utilities, and access to finance; and the business environment, particularly government regulations affecting trade and governance and institutional quality. The rest of the report is structured as follows: Section two examines overall trends in trade flows, including the growth of exports and imports, the degree of trade openness, and the recent evolution in foreign direct investment flows. In Section three, the authors concentrate on export outcomes, analyzing the sectoral composition, the growth orientation, and degree of diversification of Moldovan exports. The authors also analyze the evolution in the quality and sophistication of exports and the survival of export relationships in different markets and sectors. In the second part of the report, the authors look at productivity dynamics of Moldovan firms in comparative perspective, and then investigate the impact of access to finance, backbone services, trade and customs regulations, and corruption on firm productivity. The authors conclude this report with policy recommendations to improve Moldova's export competitiveness and increase the product and market scope, quality, and sophistication of its export basket.